Uma Perspetiva Multidimensional do Tratamento da Enxaqueca - Tânia Faia; Sílvia Morais; Andreia Rosa; Joana Santos; Bruno Sepodes (Formifarma, LDA., 2012)
Migraine is highly prevalent, affecting the quality of life of the patients and their families. Given its high economical impact, it is considered by the World Health Organization the 19th cause of disability due to illness. The prevention and treatment of the migraine are a challenge for the health professionals, who face a wide variety of drugs available, as well as varied symptoms and demands by the patients. As such, it is important that these health professionals have the knowledge and information needed to understand the migraine in its several perspectives. This review is intended to systematize the different therapeutic, pharmacological and non pharmacological approaches of the migraine.